Pengaruh Content Marketing, Copywriting dan Free Gift Terhadap Keputusan Pembelian Produk Danolshop Jombang - Andin Putri Assakinah; Eny Setyariningsih; M. Syamsul Hidayat (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
The aim of this study was to examine how content marketing, copywriting, and free gifts impact customers’ decisions to purchase products from Danolshop Jombang. The research utilized a quantitative approach with SPSS software for analysis. The sampling method employed was a non-probability sampling technique with a purposive sampling strategy. Data was gathered from 97 respondents who had made at least one purchase from Danolshop Jombang through a questionnaire. The data analysis methods included validity testing, reliability testing, classical assumption testing, multiple linear regression, and hypothesis testing. The results indicated that content marketing has a significant impact on the decision to purchase Danolshop Jombang products, whereas copywriting and free gifts do not individually influence the purchase decision. However, content marketing, copywriting, and free gifts collectively influence the decision to purchase Danolshop Jombang products.